A case of malign insulinoma diagnosed with liver metastasis. (27th January 2023) - Şehit Kara, Canan; Ilik, Abdullah; Öztürk, Figen; Abdulrezzak, Ümmühan; Ibrahim Karahan, Ökkeş; Sözüer, Erdoğan; Bayram, Fahri
Abstract: Introduction: Insulinoma is a rare neuroendocrine tumor originating from pancreatic beta cells and is the most common cause of hyperinsulinemic hypoglycemia. Herein, a rare case of metastatic insulinoma in which many treatment alternatives were used will be presented. Clinical Case: A 52-year-old male patient with no known history of chronic disease applied to us with complaints of numbness in the hands, inability to wake up in the morning and fainting. The patient, who worked as a professional referee, stated that he went to football matches with sugar in his pocket and ate sugar when he felt bad during the football matches. The patient needed to eat many times during the day. It was learned that the patient was treated with the diagnosis of transient ischemic attack and vertigo in another hospital where he applied with these complaints. In our hospital, random glucose was determined as 30 mg/dl. Prolonged fasting test was performed. Plasma glucose: 28 md/dl, insülin: 30, 81 Uıu/ml, c-peptid 6, 17 ng/ml were measured at 6th hour of the test. In abdominal computarized tomography, a 6.5×9.5 cm mass in the tail section of the pancreas and a subcentimetric metastatic nodular lesion in liver were detected. The patient diagnosed with metastatic insulinoma and distal pancreatectomy and liver metastasectomy operations were performed. Pathological examination showed insulinoma in the pancreas and neuroendocrine tumor metastasis in the liver (figure 1 ). No hypoglycemia was seen after operation. In the postoperative 24th month, fasting plasma glucose: 176 mg/dl and HBA1c: 8.6 were found and diabetes mellitus was diagnosed, insulin detemir was started. At the postoperative 36th month, a metastatic nodular lesion was detected in the liver. Fine needle aspiration biopsy was performed and in pathological examination, neuroendocrine carcinoma metastasis is seen. Octreotide LAR 20 mg/month treatment was started. In the follow-up, another metastasis was detected in two separate foci in liver so, patient's treatment was changed to lanreotide 120 mg/month. Four sessions of radiofrequency ablation were performed to the metastatic liver lesions. The patient is still being followed up by us and has no complaints of hypoglycemia. Plasma glucose values are in the normal range and Hba1c varies between 7.1–7.6%. Figure 1. A: Histopathological apperance of insulinoma: Cells with eosinophilic granular cytoplasm, centrally located, round nuclei B: Histopathological apperance of liver metastasis of insulinoma: a nested and trabecular growth pattern (H&E staining). Conclusion: Although insulinoma cases are mostly benign, metastatic cases can also be seen rarely. The main treatment of the disease is surgery. Somatostatin analogues can be used in postoperative recurrence or inoperable metastatic disease. Radiofrequency ablation has an important role in local treatment.